Policing dissent: social control and the anti-globalization movement - Fernandez, Luis A. (Critical issues in crime and society, 2008)
Policing dissent -- Perspectives on the control of dissent -- The anti-globalization movement -- Managing and regulating protest -- This is what democracy looks like? -- Here come the anarchists -- Law enforcement and control